Elucidating the Role of Val-Asn 95 and Arg-Gly 52 Mutations on Structure and Stability of Fibroblast Growth Factor Homologous Factor 2 - Kolli, Vidyalatha; Paul, Subhankar; Guttula, Praveen K.; Sarkar, Nandini (Protein and Peptide Letters, 2019)
Background: Fibroblast growth Factor Homologous Factors (FHFs) belong to a subclass of Fibroblast Growth Factor (FGF) family owing to their high sequence and structural similarities with FGFs. However, despite these similarities, there are properties which set them apart from FGFs. FHFs lack the secretion signal sequence unlike other FGF members, except FGF1 and 2. Unlike FGFs, FHFs are not able to bind to FGF Receptors (FGFRs) and instead have been implicated in binding to Voltage-Gated Sodium Channels (VGSCs), neuronal MAP kinase scaffold protein and islet-brain-2 (IB2). The two amino acids Arg-52 and Val95 are conserved in all FHFs and mutation of these residues lead to its inability to bind with VGSC/IB2. However, it is not clear whether the loss of binding is due to destabilization of the protein on mutation or due to involvement of Arg52 and Val95 in conferring functionality to FHFs. Objective: In the present study, we have mutated these two conserved residues of FHF2 with its corresponding FGF counterpart amino acids and studied the effects of the mutations on the structure and stability of the protein. Methods: Several biophysical methods like isothermal equilibrium denaturation study, ANS fluorescence, intrinsic fluorescence, acrylamide quenching, circular dichroism studies as well as using computational approaches were employed. Results: The single mutations were found to affect the overall stability, conformation and functionality of the protein. Conclusion: Thus, the studies throw light on the role of specific amino acids in deciding the stability, structure and functionality of proteins and will be useful for development of therapeutically engineered proteins.
Keywords: amino acids